Navigating Credit Access: Uncovering The Dynamics Within Poor Households in Vietnam - Anh, Nguyen The; Huong, Dao Thi (Journal of Ecohumanism, 2024)
In the context of Vietnam's dynamic but uneven economic landscape, the challenge of credit access for poor households signifies a critical disparity in financial inclusion. This research identifies and addresses a gap in understanding the influence of socioeconomic factors on credit accessibility for economically disadvantaged populations. To explore the impacts of household income stability, financial literacy, social norms, credit history, formal financial identity, and asset ownership, our study employs multivariate linear regression analysis to uncover the nuanced relationships between these factors and credit access. The findings reveal significant positive correlations, highlighting the complex interplay of economic and social elements in facilitating financial inclusion. These results offer valuable insights for policymakers, financial service providers, and development practitioners, suggesting targeted interventions in financial education, income stabilization, and adapting financial services to cultural contexts. Ultimately, this study provides a roadmap for enhancing financial accessibility for Vietnam's poor households, contributing to the broader goal of bridging the gap in financial inclusion within the country.